2020
DOI: 10.3389/fcell.2020.606817
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Autophagy-Related IncRNAs Signature for Prognostic Prediction and Clinical Value in Patients With Pancreatic Cancer

Abstract: Autophagy is an important bioprocess throughout the occurrence and development of cancer. However, the role of autophagy-related lncRNAs in pancreatic cancer (PC) remains obscure. In the study, we identified the autophagy-related lncRNAs (ARlncRNAs) and divided the PC patients from The Cancer Genome Atlas into training and validation set. Firstly, we constructed a signature in the training set by the least absolute shrinkage and selection operator penalized cox regression analysis and the multivariate cox regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…It can expedite the proliferation and migration of gastric cancer cells through IGF2BP3-involved ZEB1 mediated self-stabilization and PI3K/AKT signaling pathway [22,25]. LINC01559 can also accelerate the progression of cancer through the YAP protein, or by promoting autophagy in pancreatic cancer cells [23,45]. We found that patients with high expression of LINC01559 had poor survival rates.…”
Section: Discussionmentioning
confidence: 77%
“…It can expedite the proliferation and migration of gastric cancer cells through IGF2BP3-involved ZEB1 mediated self-stabilization and PI3K/AKT signaling pathway [22,25]. LINC01559 can also accelerate the progression of cancer through the YAP protein, or by promoting autophagy in pancreatic cancer cells [23,45]. We found that patients with high expression of LINC01559 had poor survival rates.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, combining transcriptomic data with genomic sequencing, mutational landscape, immune infiltrate or genetic alteration can identify additional subtypes with clinical relevance (Bailey et al, 2016;Connor et al, 2017;Brunton et al, 2020;Rashid et al, 2020). More importantly than predicting patient prognosis and disease aggressiveness, recent studies find that transcriptomic data is also good at predicting chemotherapy sensitivity for PDAC (Deng et al, 2020;Nicolle et al, 2021;Nishiwada et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…ROC curves of 1, 3, and 5 years were plotted with the survivalROC R package. Then, we conducted the performance comparison of the signature in our study (referred to as TP53Sig) with eight recently published signatures: 6-mRNA signature from Hou’s study (referred to as HouSig) [ 18 ], 4-mRNA signature from Meng’s study (referred to as MengSig) [ 19 ], 8-mRNA signature from Meng’s study (referred to as MengSig) [ 20 ], 5-mRNA signature from Wu’s study (referred to as WuSig) [ 21 ], 7-mRNA signature from Wu’s study (referred to as WuSig) [ 22 ], 10-mRNA signature from Yue’s study (referred to as YueSig) [ 23 ], 2-mRNA signature from Zhou’s study (referred to as ZhouSig) [ 24 ] and 6-LncRNA signature from Deng’s study (referred to as DengSig) [ 25 ]. ROC curves of 3 years were plotted and AUC values were calculated using the survivalROC R package.…”
Section: Methodsmentioning
confidence: 99%